A comparative study of the polarization degradation mechanisms during electric cycling in (Bi1/2Na1/2)TiO3-based relaxors. (15th March 2020) - Fan, Zhongming; Tan, Xiaoli
Abstract: The polarization degradation during electric field cycling in a ferroelectric ceramic is closely related to the phase composition. In the present work, electric biasing in-situ transmission electron microscopy (TEM) fatigue tests are conducted on relaxors of (1– x )(Bi1/2 Na1/2 )TiO3 – x SrTiO3 . It is directly observed that the ceramic of x = 0.25 features an irreversible relaxor-ferroelectric phase transition and the domain walls in the metastable ferroelectric phase sweep shorter and shorter distances during cycling. In contrast, the ceramic of x = 0.27 features a reversible relaxor-ferroelectric transition and the domain walls in the transient ferroelectric phase remain highly mobile even after 10 4 cycles. Graphical abstract: Image, graphical abstract